Operador de translação dependente da posição para o problema da barreira dupla de potencial - Vieira, Jussara Silvia Carneiro (2022)
This monograph aims to study the formalism of the position-dependent translation operator (PDTO) in the double potential barrier in order to understand the effects of metrics in quantum mechanics. The metric change generated a deformed, one-dimensional and time-independent Schrödinger equation, in which we applied the non-additive operator. For a small number of barriers, the WKB method was used. We solved this deformed equation for each of the five regions of the double barrier, with the requirement that the wave functions and their derivatives were equal in the discontinuities to determine the tunneling. Therefore, it appears that in the transmission coefficient, the constant a is changed by the non-additive operator.